Household Characteristics That Influence Simple Household Demand on Electricity - Nababan, Tongam Sihol (Universitas Muhammdaiyah Surakarta, 2015)
This research aims to analyze the characteristics of households that affect the electric energy consumption of simple households. The second objective is to analyze the probability of each of the factors affecting the electricity energy consumption of small household. The research was conducted in Medan City in the period of March 2014 to November 2014 with samples of 143 small households, the customer of PT. PLN (Persero) Medan, which use the power of electricity for TR-1 /450VA. Data were analyzed by using the logistic regression model. The estimation results indicated that (1) the higher the willingnes to pay (WTP) of households, the higher the tendency to consume elec trical energy per month. (2) the closer the households residence to the city center, the higher the tendency to consume electrical energy than of the households residence in the suburbs, (3) increasingly unfavourable response to electrical quality, the higher the opportunity to consume a greater electric power monthly.